Stress-Induced Reduction of Dorsal Striatal D2 Dopamine Receptors Prevents Retention of a Newly Acquired Adaptive Coping Strategy - Paolo Campus; Paolo Campus; Sonia Canterini; Cristina Orsini; Cristina Orsini; Maria Teresa Fiorenza; Maria Teresa Fiorenza; Stefano Puglisi-Allegra; Stefano Puglisi-Allegra; Simona Cabib; Simona Cabib (Frontiers Media S.A., 2017)
The inability to learn an adaptive coping strategy in a novel stressful condition leads to dysfunctional stress coping, a marker of mental disturbances. This study tested the involvement of dorsal striatal dopamine receptors in the dysfunctional coping with the Forced Swim test fostered by a previous experience of reduced food availability. Adult male mice were submitted to a temporary (12 days) reduction of food availability [food-restricted (FR)] or continuously free-fed (FF). Different groups of FF and FR mice were used to evaluate: (1) dorsal striatal mRNA levels of the two isoforms of the dopamine D2 receptor (D2S, D2L). (2) Forced Swim-induced c-fos expression in the dorsal striatum; (3) acquisition and 24 h retention of passive coping with Forced Swim. Additional groups of FF mice were tested for 24 h retention of passive coping acquired during a first experience with Forced Swim immediately followed by intra-striatal infusion of vehicle or two doses of the dopamine D2/D3 receptors antagonist sulpiride or the D1/D5 receptors antagonist SCH23390. Previous restricted feeding selectively reduced mRNA levels of both D2 isoforms and abolished Forced Swim-induced c-fos expression in the left Dorsolateral Striatum and selectively prevented 24 h retention of the coping strategy acquired in a first experience of Forced Swim. Finally, temporary blockade of left Dorsolateral Striatum D2/D3 receptors immediately following the first Forced Swim experience selectively reproduced the behavioral effect of restricted feeding in FF mice. In conclusion, the present results demonstrate that mice previously exposed to a temporary reduction of food availability show low striatal D2 receptors, a known marker of addiction-associated aberrant neuroplasticity, as well as liability to relapse into maladaptive stress coping strategies. Moreover, they offer strong support to a causal relationship between reduction of D2 receptors in the left Dorsolateral Striatum and impaired consolidation of newly acquired adaptive coping.